Characterization of Antimicrobial Resistance Genes of Pasteurella multocida Isolated from Diseased Chickens in Egypt - Bedier, ET; Labib, SR; Ahmed, AM (Journal of the Hellenic Veterinary Medical Society, 2022)
In this study, the prevalence of Pasteurella multocida in diseased chickens, capsular genotyping, antimicrobial resistance patterns and some resistance genes were determined. Lungs, liver and spleen samples were collected from 250 diseased chickens from layers and broiler flocks from El-Gharbia and Kafr El-Sheikh governorates in Egypt for isolation of P. multocida in the period from June 2018 to December 2019. Confirmatory identification was done by using PCR for capsular type A antigen. P. multocida was isolated from 3.6 % of the diseased chicken. Six isolates of P. multocida that examined for detection of capsular type A showed positive results. Antimicrobial resistance patterns were evaluated for all isolates against twenty antimicrobial agents and the results showed 100% resistance totrimethoprim/sulfamethazole, oxacillin and nitrofurantion. Also, strains expressed highly resistant to penicillin, chloramphenicol, rifampicin and ampicillin , while they were sensitive to norfloxacin, clindamycin, cephalexin and cefotaxime. The antimicrobial resistance genes were detected by using PCR and the results showed that all isolates harbored β-lactam-resistantgene BlaROB-1 (100%), followed by sulfonamide resistant gene sul1 (50%), tetracycline-resistant gene tetH (33.3%) and trimethoprim-resistant dihydrofolate reductase dfrA (16.6%).